Evaporative moisture sources of Colorado's Front Range: a case study of the exceptionally wet May-July season of 2023 - Humphreys, Katherine V., author; Keys, Patrick W., advisor; Schumacher, Russ S., committee member; Davenport, Frances V., committee member (Colorado State University. Libraries, 2025)
In 2023, some of Colorado's eastern plains experienced its wettest three-month period (May - July) out of 129 years of record (Colorado Climate Center, 2024). This extreme precipitation led to flash flooding, road washouts, and significant property damage among Colorado communities along the Front Range including Denver, Boulder, and Fort Collins. Although much is known about the seasonality of precipitation in Colorado, few studies have explored the evaporative origin of precipitation in the Front Range. To better anticipate and understand extreme precipitation events across the Front Range, we investigated the evaporative origin of 2023's extreme precipitation and how it compares to moisture sources during the previous 23 years. Specifically, this study uses the Water Accounting Model 2 Layers (WAM2layers) and hourly ERA5 reanalysis data to quantify the sources of precipitation in Colorado's Front Range during the early summer of 2023 and over the past 23 years (2000-2023). Our moisture source analysis reveals that for the Front Range region in May-July of 2023: (1) the three primary moisture sources were the Pacific Ocean, the western United States, and Colorado itself, contributing just over 66.2% of total precipitation; (2) while these sources are historically dominant, terrestrial contributions and local moisture recycling (i.e., precipitation that recently evaporated from within the Front Range) accounted for a significantly larger share than in prior years; (3) moisture sources in May-July 2023 were a statistical outlier in terms of the magnitude of moisture contributed to the Front Range, forming a cluster of its own relative to the past 24 years; and (4) between the two most dominant modes of variability, 2023 aligns more with a basin-wide pulsing pattern rather than a north-south dipole pattern of moisture sources. This research provides new insights into the extreme rainfall in the summer of 2023 as well as the historical origins of warm-season precipitation in the Front Range.
Keywords: evaporative sources; Front Range; wet season; extreme precipitation; Colorado; moisture sources